FROM ACADEMIC PROFICIENCY TO RELIGIOUS AFFILIATION: THE IMPACT OF SCHOOL ZONING POLICIES ON STUDENT DIVERSITY - Hendrik, Herman; W. Nurrochsyam, Mikka; P. Putra, Romeyn; Murdiyaningrum, Yunita (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2024)
Zoning-based New Student Admission is a policy designed to allocate students to schools based on their area of residence. This policy aims to ensure equitable access to education and promote social diversity within the school environment. This paper investigates the impact of the zoning-based New Student Admission system on student diversity in schools. The school zoning policy has the potential to modify the levels and dimensions of student diversity. Schools are required to admit the largest quota of students through the zoning route, resulting in a student body that reflects the composition of the local community. This research is significant because previous studies have primarily focused on administrative and academic aspects. Employing a qualitative methodology, including online focus group discussions (FGDs) as a data collection technique, this study found that schools labeled as "excellent" or "prestigious," particularly those situated in urban centers, reported increased student diversity following the implementation of the school zoning policy. This shift in diversity encompasses not only academic ability but also economic background, ethnicity, regionality, and religion. The study recommends that schools and teachers enhance their capacity to manage student diversity as a consequence of the school zoning system. Abstrak: Penerimaan Peserta Didik Baru berbasis zonasi merupakan kebijakan yang diterapkan untuk mendistribusikan siswa ke sekolah-sekolah berdasarkan wilayah tempat tinggal mereka. Kebijakan ini bertujuan untuk memastikan pemerataan akses pendidikan dan mendorong keberagaman sosial di lingkungan sekolah. Artikel ini mengkaji dampak dari sistem Penerimaan Peserta Didik Baru berbasis zonasi terhadap keragaman siswa di sekolah. Kebijakan zonasi sekolah memberikan peluang untuk mengubah tingkat dan aspek keragaman siswa. Hal ini disebabkan oleh mandat bagi sekolah untuk menerima siswa dengan kuota terbesar dari jalur zonasi, yang berarti komposisi siswa akan mencerminkan komposisi masyarakat yang tinggal di sekitar sekolah. Penelitian ini penting karena penelitian-penelitian sebelumnya lebih banyak berfokus pada aspek administratif dan akademis. Berdasarkan studi kualitatif yang menggunakan FGD daring sebagai teknik pengumpulan data, studi ini menemukan bahwa sekolah-sekolah yang dilabeli sebagai sekolah unggulan atau favorit dan berlokasi di tengah kota umumnya mengalami peningkatan keberagaman siswa setelah penerapan kebijakan zonasi sekolah. Perubahan keberagaman tersebut tidak hanya terjadi dalam hal kemampuan akademik, tetapi juga dalam hal latar belakang ekonomi, etnisitas atau kedaerahan, dan agama. Rekomendasi dari studi ini adalah bahwa sekolah dan guru perlu meningkatkan kapasitas mereka dalam mengelola keragaman siswa sebagai konsekuensi dari adanya sistem zonasi sekolah.